LESLIE MATRIX CONSTRUCTION AND ITS PROPERTIES IN PREDICTING THE SIZE OF THE FEMALE POPULATION - Patty, Dyana; Leleury, Z. A.; Popla, J. A. (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2024)
The growth of the female population needs to be considered because if the female population is not controlled, it is feared that it could trigger a population explosion. Using the Leslie matrix, this study aimed to predict the number and growth rate of the female population in Batugajah Village, Mdona Hyera Subdistrict, Southwest Maluku Regency. Based on the results of the study, the female population in Batugajah Village, Mdona Hyera Subdistrict, Southwest Maluku Regency, is predicted to be 157 people in 2021, 150 people in 2022, and 142 people in 2023. Furthermore, the most significant positive eigenvalue is 0.6521, which indicates that the population growth rate will tend to decrease.